(untitled) (Al-Qamar, 2019)
The conventional interest free banking system based on ethical principles of Islam seemed to be impracticable. Nobody was prepared to believe that banks could be established and made sustainable without interest. However, banking system was Islamized by serious efforts of Muslim Scholars and consequently, interest free banks were established in some Muslim countries and some Non-Muslim countries have set-up such interest free banking systems. A group of contemporary Muslim Scholars disapproves of such Banking system and believes it to be impermissible as well. They have objections against this new way of Islamic Banking initiated by some other contemporary Muslim Scholars. They believe that this new way of banking is another prototype of subtly banking with interest. Thus, according to their hypothesis it cannot be termed as true Islamic Banking.